Kinematic measures and stroke rate variability in elite female 200-m swimmers in the four swimming techniques: Athens 2004 Olympic semi-finalists and French National 2004 Championship semi-finalists - Hellard, P.; Dekerle, J.; Avalos, M.; Caudal, N.; Knopp, M.; Hausswirth, C. (Journal of Sports Sciences, 2008)
The aim of this study was to assess stroke rate variability in elite female swimmers (200-m events, all four techniques) by comparing the semi-finalists at the Athens 2004 Olympic Games (n = 64) and semi-finalists at the French National 2004 Championship (n = 64). Since swimming speed (V) is the product of stroke rate (SR) and stroke length (SL), these three variables and the coefficient of variation of stroke rate (CVSR) of the first and second 100 m were determined (V1, V2; SR1, SR2; SL1, SL2; CVSR1, CVSR2) and differences between the two parts of the events were calculated (V; SR; SL; CVSR). When the results for the four 200-m events were analysed together, SR1, SR2, SL1, and SL2 were higher ( = 0.05, P < 0.001) and V, SR, and CVSR were lower (P < 0.01) in the Olympic group than in the National group. The Olympic-standard swimmers exhibited faster backstrokes and longer freestyle strokes (P < 0.05). Both CVSR1 and CVSR2 were lower for freestyle and backstroke races in the Olympic group than in the National group (P < 0.001). Our results suggest that stroke rate variability is dependent on an interaction between the biomechanical requisites of the task (techniques) and the standard of the swimmer.